2010
DOI: 10.1177/1049909110381883
|View full text |Cite
|
Sign up to set email alerts
|

The Stresses of Hospice Volunteer Work

Abstract: The purpose of this phenomenological study was to explore the interpretation of stress, the appraisal of the stressors, as well as the top stressors experienced by hospice volunteers. Individual semistructured interviews were conducted with 15 hospice volunteers. The interviews were digitally recorded, transcribed, and analyzed, using qualitative research methods. Although the results indicated that the hospice volunteers did not perceive their work as stressful, 2 main themes regarding challenging experiences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 9 publications
0
26
0
6
Order By: Relevance
“…In addition to the attention to the motives and characteristics of volunteers, which is common across all forms of volunteering research (Wilson & Musick , Yeung , Musick & Wilson , Hustinx et al . ), palliative care volunteering has also attracted interest regarding the stresses of end‐of‐life work and how volunteers cope in an environment of death and dying (Brown , MacLeod et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the attention to the motives and characteristics of volunteers, which is common across all forms of volunteering research (Wilson & Musick , Yeung , Musick & Wilson , Hustinx et al . ), palliative care volunteering has also attracted interest regarding the stresses of end‐of‐life work and how volunteers cope in an environment of death and dying (Brown , MacLeod et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic literature review by Morris et al (2013) found no fewer than 103 articles published between 2000 and 2011 related to palliative care services and volunteering. In addition to the attention to the motives and characteristics of volunteers, which is common across all forms of volunteering research (Wilson & Musick 1997, Yeung 2004, Musick & Wilson 2008, Hustinx et al 2010, palliative care volunteering has also attracted interest regarding the stresses of end-of-life work and how volunteers cope in an environment of death and dying (Brown 2011, MacLeod et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Értesítheti az orvost arról, hogy valamely beteg segítségre szorul. Összegezve: alapos tréning után minden olyan tevékenységet végezhet, melyhez rendelkezik megfelelő kompetenciákkal, mely megfelel az intézményi szabályzatnak és egybeesik a beteg és családjának erre vonatkozó igényeivel (Brown, 2011a).…”
Section: Az öNkéntesség Helye a Hospice-banunclassified
“…A hospice önkéntesség abbahagyásának okait vizsgálva leginkább a személyes körülményeket találjuk, például a munkahely változása vagy a költözés, valamint a fizetett munka terhelésének növekedése és a kiábrándulás (Claxton-Oldfield & Claxton-Oldfield, 2008a;Thomas & Finch, 1990). A lemorzsolódás másik lehetséges oka a kezdeti magas szintű szorongás és halálfélelem, valamint a családi és munkahelyi terhelés növekedése (Amenta, 1984;Brown, 2011a;Paradis & Usui, 1987, 1989, azonban korábban már szó esett arról, hogy ez a szorongás általában csak az első évben okoz nehézséget.…”
Section: A Hospice öNkéntesség Motivációs Háttereunclassified
See 1 more Smart Citation